2015
DOI: 10.1134/s0022476615010138
|View full text |Cite
|
Sign up to set email alerts
|

A new pentacoordinate polymeric copper(II) complex with 2-amino-2-methyl-1,3-propandiol: Structural investigations using XRD and DFT

Abstract: A novel mononuclear copper complex [Cu(NH 2 mpdH)(NH 2 mpd) 2 Cl] (1) is synthesized from 2-amino-2methyl-1,3-propandiol (ampdH 4 ). The crystal structure of (1) is determined using X-ray diffraction studies. The copper complex crystallizes in the triclinic space group P-1(2) with a = 6.10.48 (4) Å, b = 10.0915(7) Å, c = 10.9249(9) Å, α = 95.925(6)°, β = 101.830(6)°, γ = 90.637(5)°, V = 649.53(95) Å 3 and Z = 2. The central copper(II) atom in (1) is coordinated by three oxygen and two nitrogen atoms possessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Furthermore, the pyridyl N atoms are considered strongly coordinated to the metal with a bond length of Cu–N of 1.9356(12) Å, while the oxygen and chlorine atoms of the equatorial plane form weaker connections with the central metal with a distance ranging from 2.0305(12) to 2.2228(4) Å ( Table S1 ). All of these values are consistent with those found for other comparable systems [ 52 , 53 , 54 , 55 , 56 ]. To differentiate between trigonal bipyramidal and square pyramidal coordination centers, Addison et al suggested the “ τ 5 ” parameter using the following Equation [ 57 ]: where β > α represents the coordination center’s two largest valence angles.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the pyridyl N atoms are considered strongly coordinated to the metal with a bond length of Cu–N of 1.9356(12) Å, while the oxygen and chlorine atoms of the equatorial plane form weaker connections with the central metal with a distance ranging from 2.0305(12) to 2.2228(4) Å ( Table S1 ). All of these values are consistent with those found for other comparable systems [ 52 , 53 , 54 , 55 , 56 ]. To differentiate between trigonal bipyramidal and square pyramidal coordination centers, Addison et al suggested the “ τ 5 ” parameter using the following Equation [ 57 ]: where β > α represents the coordination center’s two largest valence angles.…”
Section: Resultssupporting
confidence: 92%
“…The structures were optimized using Gaussian 09 software [35] and calculated for an isolated molecule using DFT [36] at the B3LYP/6-31G(d,p) [37,38] level of theory for the ligand and B3LYP/LanL2DZ [39] for the complex [40,41] as well as for NBO analysis. The X-ray structural data of complex 1 was used as input for the theoretical calculations.…”
Section: Computational Detailsmentioning
confidence: 99%